Synthesis and structural characterization of x (wt.%) MoO3/MCM-41 Catalysts for ethylbenzene dehydrogenation - Thu et al, Hoa Huu (Vietnam Journal of Chemistry, 2014)
Two catalysts series of x (wt.%) MoO3 (x=3; 6; 9) oxides dispersed onto the surface of MCM-41 support by different methods: solution impregnation and solid-state thermal spreading were prepared and characterized by XRD, N2 adsorption-desorption, SEM, TEM. MoO3 loading influences on catalysts morphology. The catalytic activity and selectivity of these catalysts in vaporous phase dehydrogenation of ethybenzene to styrene were studied. The results showed a high activity and selectivity of catalyst having MoO3 loading of 3 wt. % obtained by precursor’s solution impregnation method.